Prospecting for voids with vertical radar profiling - IOANNIS, I. F. (Bulletin of the Geological Society of Greece, 2001)
Vertical Radar Profiling measurements were conducted to image subsurface cavities encountered in Akrotiri Archaeological Excavations area on Thera Island. The vertical radar profiling technique is able to explore much deeper than conventional surface GPR because it uses wells. The transmitting-receiving antenna unit was moved within the excavated well along six vertical profile lines in equally divided positions. A local electrical resistivity survey preceded the GPR profiles to investigate if the conductivity of the pyroclastic formation satisfies the presuppositions to conduct GPR measurements. The vertical GPR profiles revealed locations where cavities exist but they were unable to show their shape and extent. Cross-well seismic tomography images supported the vertical radar profiling results.